The impact of agricultural technological innovation on residents’ health and its spatial effects - Zhao, Yuan; Cui, Shaobo; Xing, Yunfeng (Frontiers in Public Health, 2025)
In response to China’s vigorous promotion of health and green, low-carbon development, agricultural technological innovation, as a crucial tool for advancing sustainable development, is essential in promoting residents’ health. Based on data from 30 provinces in China from 2012 to 2022, this paper uses a two-way fixed effects model to examine the impact of agricultural technological innovation on residents’ health. Further, it analyzes the underlying mechanisms through mediation effects and spatial autoregressive models. The research findings are as follows: (1) Agricultural technological innovation can significantly promote residents’ health, with reducing non-point source pollution and improving dietary structure being two important intermediary channels; (2) Agricultural technological innovation has a significant spatial spillover effect on residents’ health, meaning that the health of residents in a region is not only directly influenced by the level of agricultural technological innovation in their region but also indirectly affected by that in neighboring regions.